Contribution of communication technology in achieving the conditions of communicative action in the university environment - The Progress University Platform as a model - NAOUAI, Aissa; HAMDAOUI, Omar (Social Sciences Journal)
The goal of this study revolves around analyzing Habermas’s theory of communicative action and the conditions for its realization through the Progress platform, as one of the products of communication technology, by referring to the critical school starting from Marxism to Habermasiancommunicativeism. There is no doubt that Habermas’s theory, with its combination of philosophy and sociology, is considered one of the most important socio-communicative theories in the twenty-first century. It aims to establish dialogue, consultation and understanding in various fields through communication. Through communication technology via the Progress platform, communicative action appears through the open and permanent communication it allows. Through the concepts of theory, and the common understanding it provides between the parties participating in the dialogue. With the results we have reached, it becomes clear to us what the Progress platform can provide as a working tool and support for producing effective communicative action by providing an environment that increases the strength and effectiveness of meaningful dialogue, which contributes to building a civilized and cohesive society based on mutual understanding among its members.